Development of DNA-Biochip for Identification of Influenza A Virus Subtypes - A. N. Shikov; E. I. Sergeeva; O. K. Demina; V. A. Ternovoy; V. V. Ryabinin; E. V. Kostina; E. M. Malkova; A. N. Sinyakov; A. P. Agaphonov (Проблемы особо опасных инфекций, 2012)
Developed was the DNA-biochip to identify subtypes of influenza A virus, pathogenic for humans. Microchip was capable of detecting H1, H3, H5-subtypes of hemagglutinin (including H1-subtype of pandemic A/H1N1(2009) influenza virus ) and neuraminidase subtypes N1,N2 of influenza virus. This microchip was successfully tested on the strains of A/H5N1 highly pathogenic avian influenza virus, A/H1N1(2009) pandemic influenza virus, A/H1N1 and A/H3N2 seasonal influenza viruses.